Systematic review comparing meropenem with imipenem plus cilastatin in the treatment of severe infections. - Edwards, S; Emmas, C; Campbell, H (2005)
OBJECTIVE: To compare the effectiveness of meropenem with imipenem plus cilastatin in the treatment of severe infections. DATA SOURCES: CENTRAL, EMBASE and MEDLINE were searched for abstracts and papers. All searching was completed in March 2004. No restriction was placed on language. STUDY SELECTION: Randomized controlled trials of adult patients with severe infections treated with meropenem or imipenem plus cilastatin at an equal dose, on a gram-for-gram basis, and with the same dosing regimen. DATA EXTRACTION: Two reviewers independently assessed papers against the inclusion/exclusion criteria and for methodological quality with differences in opinion adjudicated by a third party. Data were extracted on clinical response, bacteriologic response, mortality and adverse events. DATA SYNTHESIS: A total of 27 trials met the inclusion criteria. Meta-analyses were carried out using a Fixed Effects model. Results demonstrated that when compared to imipenem plus cilastatin, meropenem is associated with a significantly greater clinical response (Relative Risk 1.04; 95% Confidence Interval: 1.01-1.06), a significantly greater bacteriologic response (RR 1.05; 95% CI: 1.01-1.08), a non-significant reduction in mortality (RR 0.98; 95% CI: 0.71-1.35), and a significantly lower adverse event rate (RR 0.87; 95% CI: 0.77-0.97). CONCLUSIONS: This systematic review demonstrates that meropenem compared to imipenem plus cilastatin has a significantly greater clinical and bacteriologic response with a significant reduction in adverse events. There was no evidence of heterogeneity or publication bias and the analyses were robust to changes in the inclusion/exclusion criteria and use of a Random Effects model.